COMPARISON OF ENGLISH AND FRENCH RIDDLES - Nishonova Shaxnoza Muhammedjonova (Galaxy International Interdisciplinary Research Journal, 2023)
In this work Language riddles have words at their core and demonstrate the many nuances of communication. They take an alternative approach to language and expose words with unexpected meanings. These riddles demonstrate the intricacies involved at all levels of discourse and show how extraordinary words and sentences can be.